Podnikatelský záměr – založení relaxačního centra - Spurná, Kamila (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Hlavním cílem této bakalářské práce je zpracování podnikatelského záměru pro založení relaxačního centra v městě Brno. Zabývá se problematikou analýzy vnitřního a vnějšího prostředí, průzkumem trhu a konkrétními návrhy na uskutečnění. Účelem práce je posoudit, zda bude záměr realizovatelný či nikoliv.

The main object of the thesis is a the create a business plan for setting up a relaxation center in the town Brno. It deals with issues of analysis of internal and external environment, market research and concrete proposals for implementation. The purpose of this work is to assess whether the project will be feasible or not.
Business Plan – Establishment of a Relaxation Center
Keywords: Podnikatelský záměr; relaxační centrum; SWOT analýza; SLEPT analýza; zdravý životní styl; Business plan; relaxation centre; SWOT analysis; SLEPT analysis; healthy lifestyle